2017
DOI: 10.1007/s00425-017-2696-6
|View full text |Cite
|
Sign up to set email alerts
|

The R2R3-MYB TT2b and the bHLH TT8 genes are the major regulators of proanthocyanidin biosynthesis in the leaves of Lotus species

Abstract: By exploiting interspecific hybrids and their progeny, we identified key regulatory and transporter genes intimately related to proanthocyanidin biosynthesis in leaves of Lotus spp. Proanthocyanidins (PAs), known as condensed tannins, are polymeric flavonoids enriching forage legumes of key nutritional value to prevent bloating in ruminant animals. Unfortunately, major forage legumes such as alfalfa and clovers lack PAs in edible tissues. Therefore, engineering the PA trait in herbage of forage legumes is para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 67 publications
4
22
0
Order By: Relevance
“…Accumulating evidence demonstrates that TT8 is a central component of the well‐conserved complex that controls flavonoid accumulation in various crops (Escaray et al , ; Li et al , ; Li et al , ; Lim et al , ; Nemesio‐Gorriz et al , ; Schaart et al , ). Taking into account the close phylogenetic relationship between Arabidopsis and Brassica , TT8 gene homologs could play comparable roles in Brassica species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence demonstrates that TT8 is a central component of the well‐conserved complex that controls flavonoid accumulation in various crops (Escaray et al , ; Li et al , ; Li et al , ; Lim et al , ; Nemesio‐Gorriz et al , ; Schaart et al , ). Taking into account the close phylogenetic relationship between Arabidopsis and Brassica , TT8 gene homologs could play comparable roles in Brassica species.…”
Section: Introductionmentioning
confidence: 99%
“…In A. thaliana, a ternary complex (known as the MBW complex) comprising three TF regulators, namely AtMYB123/TT2 (R2R3-MYB), TT8 (basic helix-loop-helix, bHLH) and TTG1 (WD40 protein), plays a key role in activating PA-specific genes in seed coat development (Xu et al, 2014(Xu et al, , 2015. Accumulating evidence demonstrates that TT8 is a central component of the well-conserved complex that controls flavonoid accumulation in various crops (Escaray et al, 2017;Li et al, 2016;Lim et al, 2017;Nemesio-Gorriz et al, 2017;Schaart et al, 2013). Taking into account the close phylogenetic relationship between Arabidopsis and Brassica, TT8 gene homologs could play comparable roles in Brassica species.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of seed color in most plant species is due to the deposition of PAs within the endothelial layer of the inner integument of the seed coat [13]. Previous studies demonstrated that TT8 played a key role in regulating PAs accumulation in various plants [18,19]. In this paper, mutation of the NtAn1, the TT8 homolog genes in tobacco, generated yellow-seeded phenotype (Fig.…”
Section: Mutation Of Ntan1 Genes Resulted In Yellow Seed Coatmentioning
confidence: 62%
“…Most recently, targeted mutation of the TT8 homologs through CRISPR-Cas9 system in Brassica napus also generated yellow-seeded phenotype [12]. Homologs of TT8 gene were also reported to be involved in PAs biosynthesis in diverse plant species, including Medicago truncatula, Lotus corniculatus, and Raphanus sativus [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Its core conserved domain contains approximately 60 amino acid residues [6]. The bHLH has been shown to be involved in numerous biological processes, including stress resistance [7][8][9], growth and development [10,11], signal transduction [12,13] and synthesis [14][15][16]. The first bHLH transcription factor was discovered in maize, where its function is involved in the synthesis of anthocyanins [17].…”
Section: Introductionmentioning
confidence: 99%